Histidine-tryptophan-ketoglutarate solution versus blood cardioplegia in cardiac surgery: A propensity-score matched analysis (2018)
Background: Choosing a cardioplegic solution is a significant issue in modern cardiac surgery. Although different options are available, the optimal strategy for myocardial protection has not been established. The aim of this study was to compare intraoperative and postoperative effects of histidine–tryptophan–ketoglutarate (HTK) solution with those of standard blood cardioplegia with St Thomas No 2 solution. The study was conducted using a large cohort of adult patients undergoing complex cardiac surgery. Methods: This study was a single center retrospective review of prospectively collected data. Between January 2008 and December 2015, 4480 patients underwent cardiac surgery using cardiopulmonary bypass (CPB) and cardioplegic arrest. Patients were divided into a blood cardioplegia group (n = 3852) and an HTK solution group (n = 628). Propensity score matching was used to adjust for differences between the two groups, and 292 matched pairs were identified. The primary end point was Intensive Care Unit (ICU) length of stay (LOS). Secondary end points included intraoperative changes in serum sodium concentration, readmission to ICU, transfusion of blood products, 30-day hospital readmission, 30-day mortality, and the incidence of major postoperative complications. Results: No significant differences were found between the matched groups with regard to baseline characteristics. Aortic cross-clamp and CPB times were longer for the blood cardioplegia (147.4 versus 132.8 min; P less than .001). Administration of HTK solution was associated with acute and transient hyponatremia (141 versus 130 mmol/L; P less than .001). ICU LOS was comparable between the groups (5.4 versus 5.4 days; P = .585). No significant differences were noted in any other secondary end point. Conclusions: During complex cardiac surgery, both cardioplegia techniques were equivalent in terms of early clinical outcomes. © 2018 Forum Multimedia Publishing, LLC.